A Bibliometric Analysis of Public Transportation Management-Based Sustainable Development - Vera Sulistyana Devi Cristyani; Kismartini Kismartini (Universitas Sebelas Maret, 2025)
Sustainable transport is one way to address the challenges associated with urbanization and support environmentally friendly, inclusive, and innovative city development. Trend analysis, evolution of themes and research opportunities in the field of public transport management with sustainable development perspective: A bibliometric study the research data was collected in the Scopus database by requesting publications using keywords,